Pengaruh Media Belajar Big Book Terhadap Minat Belajar IPS Siswa Kelas VII Di MTsN 5 Majalengka - Fasya Hamdan Akbar; Etty Ratnawati; Septiani Resmalasari (Publikasi Berkala Pendidikan Ilmu Sosial, 2024)
This research aims to find out how the Big Book learning media is applied in the social studies learning process, to find out students' interest in learning, and the influence of using Big Book learning media on students' learning interests. This quantitative research uses a one-shot case study design, using 32 respondents. The data collection techniques used are observation, questionnaires, and documentation. Data analysis techniques used were a percentage scale, validity test, reliability test using the Kuder Ricardson-20 method, normality test, linearity test, Pearson Product Moment correlation test, determination test, simple linear regression test, and hypothesis test. The results of this research are (1) the level of application of Big Book learning media is around 75.71%, included in the strong category (2) the level of interest in learning social studies of students using Big Book media is 80.92%, included in the strong category (3) T count results 7.122 > T table 2.042 or sig value .000 < 0.05, which means it can be concluded that Ho is rejected and Ha is accepted, meaning that there is a significant influence between the Big Book learning media on students' interest in learning in the social studies learning process.